Penerapan Model PBL Berbantuan Media Augmented Reality Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Sulhaliza, Ammylia Prihatini; Ermawati, Diana; Setiawaty, Rani (Absis: Mathematics Education Journal, 2025)
This article explains the results of research on the use of Problem-Based Learning (PBL) model supported by Augmented Reality media to improve students' ability to solve mathematical problems. This research was motivated by the low interest of elementary school students at SD N 2 Panjunan in mathematics, which impacted their low ability to solve mathematical problems. Additionally, the use of technology in learning was still very minimal, and the learning models used lacked variety, resulting in suboptimal learning outcomes. This research employed a quantitative experimental method with a pretest-posttest design on one group, consisting of 25 fifth-grade students at SD 2 Panjunan. Data were obtained through essay-type test questions analyzed using the N-Gain Score test. The results showed an improvement in problem-solving ability of 30.9%, with an average score before learning (pretest) of 54.80 and after learning (posttest) of 85.68. The N-Gain value of 68.06% falls into the moderate improvement category. From these results, it can be concluded that the use of the PBL model assisted by Augmented Reality media can improve the ability of fifth-grade students at SD 2 Panjunan to solve mathematical problems.